DEVELOPMENT OF SOFT SKILL-BASED INTERACTIVE MEDIA ON THEMATIC LEARNING AT ELEMENTARY SCHOOLS - Umayah, Urip; Winandika, Gigih (Universitas Muhammadiyah Purwokerto, 2024)
The purpose of this research is to develop soft skill-based interactive media, to know the quality of soft skill-based interactive media in thematic learning, and to know the level of effectiveness of using soft skills-based interactive media. This study uses the type of research R & D (Research and Development). The stages of developing soft skill-based interactive media are modified into four stages, namely analysis, design, development, and implementation. The interactive media testing developed has met the criteria of being valid, quality and effective. Validity is declared after instrument validation and product validation have been carried out by media experts. Soft skill-based interactive learning media is said to be of very high quality because teacher and student assessments of learning media are in the very quality category. Soft skill-based learning media is said to be effective because it has met the criteria for assessing teacher activity on learning media, which is in the very effective category. It was concluded that the soft skill-based interactive learning media developed had met the categories of validity, quality and effectiveness so that it was feasible to be used and developed not only in public and private elementary schools.